Global Infodemiology of COVID-19: Analysis of Google Web Searches and Instagram Hashtags - Rovetta, Alessandro; Bhagavathula, Akshaya Srikanth (JMIR Publications, 2020)
BackgroundAlthough "infodemiological" methods have been used in research on coronavirus disease (COVID-19), an examination of the extent of infodemic moniker (misinformation) use on the internet remains limited. ObjectiveThe aim of this paper is to investigate internet search behaviors related to COVID-19 and examine the circulation of infodemic monikers through two platforms-Google and Instagram-during the current global pandemic. MethodsWe have defined infodemic moniker as a term, query, hashtag, or phrase that generates or feeds fake news, misinterpretations, or discriminatory phenomena. Using Google Trends and Instagram hashtags, we explored internet search activities and behaviors related to the COVID-19 pandemic from February 20, 2020, to May 6, 2020. We investigated the names used to identify the virus, health and risk perception, life during the lockdown, and information related to the adoption of COVID-19 infodemic monikers. We computed the average peak volume with a 95% CI for the monikers. ResultsThe top six COVID-19-related terms searched in Google were "coronavirus," "corona," "COVID," "virus," "corona virus," and "COVID-19." Countries with a higher number of COVID-19 cases had a higher number of COVID-19 queries on Google. The monikers "coronavirus ozone," "coronavirus laboratory," "coronavirus 5G," "coronavirus conspiracy," and "coronavirus bill gates" were widely circulated on the internet. Searches on "tips and cures" for COVID-19 spiked in relation to the US president speculating about a "miracle cure" and suggesting an injection of disinfectant to treat the virus. Around two thirds (n=48,700,000, 66.1%) of Instagram users used the hashtags "COVID-19" and "coronavirus" to disperse virus-related information. ConclusionsGlobally, there is a growing interest in COVID-19, and numerous infodemic monikers continue to circulate on the internet. Based on our findings, we hope to encourage mass media regulators and health organizers to be vigilant and diminish the use and circulation of these infodemic monikers to decrease the spread of misinformation.